Nutrigenomics of Natural Antioxidants in Broilers - Ioanna Kouvedaki; Athanasios C. Pappas; Peter F. Surai; Evangelos Zoidis (MDPI AG, 2024)
The broiler industry supplies high-quality animal protein to the world. The ban of antibiotics as growth promoters has opened the way for plenty of phytochemicals and antioxidants to be explored. This study summarizes the use of natural antioxidants in a broiler diet as a way through which to deal with stressors, as well as their effects on the expression of various genes. The transcriptional factors and genes involved in the regulation of redox homeostasis are described and emphasis is placed on nuclear factor erythroid 2-related factor 2 and nuclear factor kappa B. Sources such as fruits, vegetables, spices, mushrooms, and algae contain numerous natural antioxidant compounds. The antioxidant activity of these compounds has also been confirmed at the genome level. This study focuses on the regulation of oxidative stress-related genes, as well as on genes that regulate the inflammatory response, apoptosis, response to heat stress, lipid metabolism, and the intestinal barrier status. The natural compounds presented include, but are not limited to, the following: rutin, lycopene, magnolol, genistein, hesperidin, naringin, quercetin, curcumin, bisdemethoxycurcumin, resveratrol, astaxanthin, squalene, pterostilbene, protocatechuic acid, taraxasterol, myricetin, and proanthocyanidins. Several studies have revealed a dose-dependent action. Future studies should focus on the role of phytogenic compounds as antibiotic alternatives in relation to gut microbiota and their role in eubiosis.